Safety Evaluation of the Novel Cocktail of Monoclonal Antibodies for Postexposure Prophylaxis in Category III Animal Exposures - Ravish Haradanahalli Shankaraiah; N. R. Ramesh Masthi; M. K. Poornima; Vinitha Kiruffi; S. Sowmyashree; Trayambak Dutta; Manish Mahajan; Samir Desai (Journal of Global Infectious Diseases)
Introduction: Rabies monoclonal antibody (mAb) is a life-saving immune-biological for postexposure prophylaxis (PEP) in all Category III animal exposures. A novel cocktail of mAbs derived using recombinant DNA technology is presently available for usage. The WHO recommends monitoring the clinical use and outcomes of mAb products. Methods: An open-label, postmarketing study was conducted at the anti-rabies clinic in the southern part of India. PEP was provided to all the study participants per the national guidelines. All the subjects were assessed for any adverse events (AEs) following PEP up to 35 days; if any, were treated free of cost at the study center. Results: The present study included 309 subjects across all age groups, 59.2% were adults, 33.3% of children, and 7.5% elderly. Majority of the patients were exposed to dogs (89.6%) and most of them had lacerations (86.3%) in different parts of their body. A total of 19 (6.2%) AEs were reported. All the AEs were local reactions, namely pain (2.6%), erythema (1.4%), tenderness (1%), induration (0.6%), and swelling (0.6%). All reported AEs were mild (Grade 1 severity) and resolved completely with symptomatic treatment. Conclusion: The novel cocktail of mAbs was safe for PEP in Category III animal exposures across all the age groups and supports its continued and improved usage for Universal Health Coverage to prevent rabies.